2003
DOI: 10.1007/s00392-003-0880-0
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in congenital cardiac disease: an increasing challenge for cardiologists and obstetricians - a prospective multicenter study

Abstract: Most women with CCD and a good functional class before pregnancy tolerate pregnancy without major problems. However, pregnancy may induce serious cardiac and obstetric complications. The specific risks require an individualized multidisciplinary patient-management by experienced physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
4
13
1
3
Order By: Relevance
“…12 The impact of pregnancy on systemic RV function in women after ASO is therefore a concern. 3, 13 In the present study, a decrease in ventricular function occurred in 2 women during their first pregnancy, in 1 during her second pregnancy and in 1 during her third pregnancy. Three of the 4 women (75%) did not return to their pre-pregnancy level of RV function.…”
Section: Trigas V Et Alsupporting
confidence: 46%
“…12 The impact of pregnancy on systemic RV function in women after ASO is therefore a concern. 3, 13 In the present study, a decrease in ventricular function occurred in 2 women during their first pregnancy, in 1 during her second pregnancy and in 1 during her third pregnancy. Three of the 4 women (75%) did not return to their pre-pregnancy level of RV function.…”
Section: Trigas V Et Alsupporting
confidence: 46%
“…3,4 In the present study we found a low rate of cardiac events during pregnancy, which is in agreement with the small amount of existing literature. [5][6][7][8] The risk of obstetric events was associated with the corrective status. The presence of an unrepaired VSD was associated with a higher risk of pre-eclampsia (8.7%).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Despite the fact that a VSD is one of the most common forms of heart disease among pregnant women, VSD-specific pregnancy data are limited. [5][6][7][8] A recent literature review of studies published between 1985 and 2007 found a total of 83 completed pregnancies among women with VSDs (combining repaired and unrepaired VSD). 9 The current consensus is that pregnancy in women with an isolated VSD is generally well tolerated, with no maternal mortality and no significant maternal or fetal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In dieses Patientenkollektiv gehören Patientinnen mit schweren kongenitalen Herzerkrankungen, die in immer größerer Zahl nach erfolgreicher operativer oder interventioneller Behandlung das Erwachsenenalter erreichen [25], sowie Patientinnen mit Klappenprothesen oder mit Vorhofflimmern [28]. Die Beratung und Versorgung dieser Patientinnen stellt hohe Anforderungen an die betreuenden Ärzte und bedingt eine interdisziplinäre Zusammenarbeit von Hausärzten, Internisten, Kardiologen und Frauenärzten.…”
unclassified